Childhood maltreatment and personality disorders in the USA: Specificity of effects and the impact of gender. (29th August 2013) - Waxman, Rachel; Fenton, Miriam C.; Skodol, Andrew E.; Grant, Bridget F.; Hasin, Deborah
ABSTRACT Childhood maltreatment increases the risk for adult personality disorders (PDs), but several PDs or maltreatment types co‐occur. Specificity of maltreatment–personality associations is poorly understood. Using a representative US population sample, we identified specific associations between maltreatment types (sexual, physical and emotional abuse and physical and emotional neglect) and PDs after controlling for basic demographics, parental psychopathology, co‐occurring maltreatment types and comorbid PD. We then examined interactions of gender and maltreatment in predicting PDs. Each maltreatment type significantly predicted three–four PDs. Borderline and schizotypal PDs were most strongly predicted by sexual abuse, antisocial by physical abuse and avoidant and schizoid by emotional neglect. Specific vulnerabilities differ by gender; maltreated boys may respond with attention seeking and girls with social withdrawal. Findings highlight the importance of evaluating all forms of maltreatment even when they co‐occur and can inform development of interventions to prevent personality pathology in at‐risk children. Copyright © 2013 John Wiley & Sons, Ltd.